Ohio Children's Hospitals' Solutions for Patient Safety: A Framework for Pediatric Patient Safety Improvement. Issue 4 (July 2016) - Lyren, Anne; Brilli, Richard; Bird, Michael; Lashutka, Nicholas; Muething, Stephen
Abstract : Objectives: Building upon their previous collective success and a clinical imperative for rapid improvement, the eight tertiary pediatric referral centers in Ohio sought to dramatically decrease the most serious types of harm that occur to hospitalized children by collectively employing high reliability methods focused on safety culture. Methods: With the support of the hospitals' executives, the Ohio collaborative obtained legal protection and built will by clearly identifying types and frequency of harm events that occur in each participating hospital and across the state. The improvement efforts were divided among task forces designed to incorporate the principles of high reliability organizations into the work of all employees, focusing primarily on the consistent application of error prevention behaviors. Results: Between January 2010 and October 2012, the serious safety event rate among the participating hospitals decreased by 55%, equating to 70 fewer children per year who experienced this most severe type of event in the participating hospitals. Between January 2011 and October 2012, all events of serious harm were decreased by 40%, meaning 18 fewer children per month suffered serious harm. Conclusion: Rapid and significant improvement in pediatric patient safety is possible through collaboration of children's hospitals dedicated to the application of high reliability principles and the noncompetitive sharing of outcomes and best practices.